Effects of Active Video Games Combined with Conventional Physical Therapy on Perceived Functionality in Older Adults with Knee or Hip Osteoarthritis: A Randomized Controlled Trial - Francisco Guede-Rojas; Cristhian Mendoza; Jorge Fuentes-Contreras; Cristian Alvarez; Bárbara Agurto Tarbes; Javiera Karina Muñoz-Gutiérrez; Adolfo Soto-Martínez; Claudio Carvajal-Parodi (Applied Sciences)
Background: Osteoarthritis (OA) leads to functional decline in older adults. This study aimed to evaluate the effectiveness of active video games (AVGs) as a complement to conventional physical therapy (CPT) in improving functional disability. Methods: Sixty participants were randomly assigned to an experimental group (EG, n = 30, 68.7 ± 5.4 years), which received CPT combined with AVGs, or to a control group (CG, n = 30, 69.0 ± 5.5 years), which received CPT alone. Sessions were performed three times a week for ten weeks. Functional disability was assessed using the WOMAC index before, during, and after the intervention. Secondary outcomes included the Global Rating of Change (GRoC), the Minimal Clinically Important Difference, and patient trajectories through functional disability strata. Results: The EG showed progressive improvements in all WOMAC scores, with moderate to large increases by the end of the intervention, while the CG only showed significant changes in the later stages. The EG demonstrated greater improvements in WOMAC pain and the GroC scale (p < 0.05), maintaining most of the gains at follow-up, whereas the CG showed regression. Additionally, the EG had a higher proportion of responders, particularly for pain, while the CG had a predominance of non-responders and adverse responders. In the EG, 70% improved their functional disability stratification compared to 50% in the CG. Conclusion: Integration of AVGs with CPT further improves perceived functional disability in older adults with OA. Future research should explore these findings further.